Improving crop productivity in sustainable agriculture - Tuteja, Narendra; Gill, Sarvajeet Singh; Tuteja, Renu (Weinheim : Wiley-Blackwell, 2013)
An up-to-date overview of current progress in improving crop quality and quantity using modern methods. With a particular emphasis on genetic engineering, this text focusses on crop improvement under adverse conditions, paying special attention to such staple crops as rice, maize, and pulses. Improving Crop Productivity in Sustainable Agriculture includes an excellent mix of specific examples, such as the creation of nutritionally-fortified rice and a discussion of the political and economic implications of genetically engineered food. The result is a must-have hands-on.
Part 1. Climate Change and Abiotic Stress Factors: Climate Change and Food Security / R.B. Singh -- Improving Crop Productivity under Changing Environment / Navjot K. Dhillon, Satbir S. Gosal, Manjit S. Kang -- Genetic Engineering for Acid Soil Tolerance in Plants / Sagarika Mishra, Lingaraj Sahoo, Sanjib K. Panda -- Evaluation of Tropospheric O Effects on Global Agriculture: A New Insight / Richa Rai, Abhijit Sarkar, S.B. Agrawal, Madhoolika Agrawal -- Part 2. Methods to Improve Crop Productivity: Mitogen-Activated Protein Kinases in Abiotic Stress Tolerance in Crop Plants: "-Omics" Approaches / Monika Jaggi, Meetu Gupta, Narendra Tuteja, Alok Krishna Sinha -- Plant Growth Promoting Rhizobacteria-Mediated Amelioration of Abiotic and Biotic Stresses for Increasing Crop Productivity / Vasvi Chaudhry, Suchi Srivastava, Puneet Singh Chauhan, Poonam C. Singh, Aradhana Mishra, Chandra Shekhar Nautiyal -- Are Viruses Always Villains? The Roles Plant Viruses May Play in Improving Plant Responses to Stress / Stephen J. Wylie, Michael G.K. Jones -- Risk Assessment of Abiotic Stress Tolerant GM Crops / Paul Howles, Joe Smith -- Biofertilizers: Potential for Crop Improvement under Stressed Conditions / Alok Adholeya, Manab Das -- Part 3. Species-Specific Case Studies: Rice: Genetic Engineering Approaches for Abiotic Stress Tolerance: Retrospects and Prospects / Salvinder Singh, M.K. Modi, Sarvajeet Singh Gill, Narendra Tuteja -- Rice: Genetic Engineering Approaches to Enhance Grain Iron Content / Salvinder Singh, D. Sudhakar, M.K. Modi -- Pearl Millet: Genetic Improvement in Tolerance to Abiotic Stresses / O.P. Yadav, K.N. Rai, S.K. Gupta -- Bamboo: Application of Plant Tissue Culture Techniques for Genetic Improvement of Dendrocalamus strictus Nees / C.K. John, V.A. Parasharami -- Groundnut: Genetic Approaches to Enhance Adaptation of Groundnut (Arachis Hypogaea, L.) to Drought / R.C. Nageswara Rao, M.S. Sheshshayee, N. Nataraja Karaba, Rohini Sreevathsa, N. Rama, S. Kumaraswamy, T.G. Prasad, M. Udayakumar -- Chickpea: Crop Improvement under Changing Environment Conditions / B.K. Sarmah, S. Acharjee, H.C. Sharma -- Grain Legumes: Biotechnological Interventions in Crop Improvement for Adverse Environments / Pooja Bhatnagar-Mathur, Paramita Palit, Ch. Sridhar Kumar, D. Srinivas Reddy, Kiran K. Sharma -- Pulse Crops: Biotechnological Strategies to Enhance Abiotic Stress Tolerance / S. Ganeshan, P.M. Gaur, R.N. Chibbar -- Improving Crop Productivity and Abiotic Stress Tolerance in Cultivated Fragaria Using Omics and Systems Biology Approach / Jens Rohloff, Pankaj Barah, Atle M. Bones -- Rose: Improvement for Crop Productivity / Madhu Sharma, Kiran Kaul, Navtej Kaur, Markandey Singh, Devendra Dhayani, Paramvir Singh Ahuja.
Includes bibliographical references and index.
Print version record.
Keywords: Crop improvement; Sustainable agriculture; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture; Crop improvement; Sustainable agriculture; Electronic books; Electronic books